Determining the components of the psychophysical readiness of police officers to use service firearms under martial law conditions (Law and Safety, 2023)
The scientific work is aimed at finding ways to improve the components of the psychophysical readiness of police officers to use service firearms. In order to solve the research tasks, an analysis of the sources of international and domestic law regulating the use of force, special means, and firearms by the police has been carried out, including the UN Code of Conduct for Law Enforcement Officials, the Declaration on the Police, Basic Principles of the Use of Force and Firearms by Officials on maintaining law and order, the Constitution of Ukraine, the Criminal Code of Ukraine, the Law of Ukraine “On the National Police”, Regulations on the organization of official training of employees of the National Police of Ukraine, Instructions on safety measures when handling weapons, Regulations on the organization of initial professional training of police officers who are first accepted on police service.The algorithm for applying coercive police measures proposed by the UN hs been considered, that is communication – persuasion – physical force – special means – firearms. A comparative characterization of the indicators of firearm owners per 100,000 population abroad with a similar indicator in Ukraine has been carried out. The peculiarities of the legal regulation of the use of coercive police measures in Ukraine under martial law conditions have been determined. The legal, social, domestic and psychophysiological factors that affect the decision-making by police officers on the possibility of using a registered firearm have been given.Based on the conducted research, the study of special literature, and the analysis of the activities of practical police officers who have at least 5 years of service, it has been established that the components of psychophysical readiness for the use of service firearms are physical, psychological, fire (shooting) and tactical-special training. Ways of a complex combination of the specified areas of psychophysical readiness for the use of service firearms have been proposed.
Keywords: police officer; service firearms; psychophysical training; stress; extreme conditions; physical qualities; medical and biological indicators.